Large tunable intrinsic gap in rhombohedral-stacked tetralayer graphene at half filling. (2nd August 2018) - Myhro, K; Che, S; Shi, Y; Lee, Y; Thilahar, K; Bleich, K; Smirnov, D; Lau, C N
Abstract: At half filling, the very flat energy bands in rhombohedral-stacked tetralayer graphene are unstable to electronic interactions, giving rise to electronic states with spontaneous broken symmetries. Using transport measurements on suspended dual-gated devices, we observe an insulating ground state with a large interaction-induced transport gap up to 80 meV, which can be enhanced by a perpendicular magnetic field, and suppressed by an interlayer potential, carrier density, or a critical temperature of 40 K. This insulating gapped state is proposed to be a layer antiferromagnet with broken time reversal symmetry.